The impact of NOS3 gene polymorphism on papillary thyroid cancer susceptibility in patients undergoing radioiodine therapy - Cerqueira, Adara Rodrigues Damasceno (2020)
Thyroid cancer is the most common endocrine cancer in the world. Noting that the NOS3 gene polymorphism interferes with nitric oxide production, this study aims to identify and analyze the NOS3 gene polymorphism in the intron 4 region in patients with papillary thyroid cancer. A case-control study was conducted with 31 papillary thyroid cancer patients of both genders who underwent thyroidectomy and treatment with sodium iodide radiopharmaceutical (131I) compared with 81 control patients. Through papillary thyroid cancer, the results were observed, compiled, and analyzed using SPSS version 25.0. The significance level of 5% was adopted. Genotypic frequencies of healthy subjects were in the Hardy-Weinberg equilibrium (P = 0.503). There was a significant genotypic difference between papillary thyroid cancer and healthy individuals (P <0.001). The BB genotype conferred a protective factor for papillary thyroid cancer (P <0.001, odds ratio (OR) 0.16; 95% confidence interval (CI) 0.06, 0.42), while the presence of the A allele appears to be a risk factor for papillary thyroid cancer (P <0.001, OR 3.54; 95% CI 1.86, 6.73). The intron 4 polymorphism of the NOS3 gene was associated with susceptibility to papillary thyroid cancer. Thus, future research into the effects of this polymorphism is essential.